An overview of archaeology and heritage in Qatar - Muhesen, Sultan; al-Naimi, Faisal; Thuesen, Ingolf (Proceedings of the Seminar for Arabian Studies, 2012)
This paper briefly summarizes the results of the fieldwork projects undertaken by the Qatar Museums Authority (QMA hereafter) in 2010-2011. The projects discussed include excavation and survey work by the Qatar Islamic Archaeology and Heritage Project at al-Zubārah, Freiha (al-Furayhah), Ruwaidah (al Ruwaydah), and Rubayqah; investigations in northern Qatar by the Qatar National Historic Environment Record project; excavations at Smaisma (Sumaysimah); and an assessment of the importance of a heritage protection programme in the old quarter of al-Asmakh, Doha.